Exploring the relationship between employee engagement, job satisfaction, and turnover intention in the hospitality industry - Sudiarta, Made; Sekarti, Ni Ketut; Sunarsa, I Wayan (YAYASAN MITRA PERSADA NUSANTARA, 2025)
The high turnover rate in the hospitality industry is a significant challenge that can negatively impact operational stability and increase costs for businesses. This research aims to examine the relationship between job satisfaction, employee engagement, and turnover intention at YJR. The study investigates how factors such as job satisfaction and employee engagement influence employees' intentions to leave the organization. Utilizing a quantitative research method, data was collected through surveys and interviews with current and former employees of the restaurant. The data were analysed using descriptive statistics and correlation analysis to determine the strength of the relationships between the variables. The results indicate that both job satisfaction and employee engagement have a significant negative impact on turnover intention. Employees who reported higher levels of satisfaction and engagement were less likely to express an intention to leave the company. Conversely, those with lower satisfaction and engagement levels were more inclined to consider exiting. Additionally, the research found that key drivers of dissatisfaction include limited career development opportunities, insufficient compensation, and a lack of recognition. The study concludes that improving job satisfaction and fostering employee engagement are critical strategies for reducing turnover at this company. Practical recommendations for management include implementing policies that enhance work-life balance, offering competitive compensation, and creating career advancement opportunities. Future research could expand on this study by examining the long-term effects of these strategies on turnover rates and exploring similar relationships in other sectors of the hospitality industry.